2008
DOI: 10.1016/j.neulet.2007.11.066
|View full text |Cite
|
Sign up to set email alerts
|

Casein kinase 1 alpha associates with the tau-bearing lesions of inclusion body myositis

Abstract: Inclusion body myositis and Alzheimer's disease are age-related disorders characterized in part by the appearance of intracellular lesions composed of filamentous aggregates of the microtubuleassociated protein tau. Abnormal tau phosphorylation accompanies tau aggregation and may be an upstream pathological event in both diseases. Enzymes implicated in tau hyperphosphorylation in Alzheimer's disease include members of the casein kinase-1 family of phosphotransferases, a group of structurally related protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 48 publications
0
16
0
Order By: Relevance
“…Recent studies demonstrated that casein kinase 1␦ also phosphorylates numerous sites of tau in vitro, as GSK-3␤ does (53) and probably in vivo as well (54), suggesting that it may also play a role in tau pathology. By using double-labeled fluorescence immunohistochemistry, casein kinase 1 isoforms were found to associate differentially with neurofibrillary and granulovacuolar degeneration lesions in AD brain (55) and with tau-bearing lesions of inclusion body myositis (56). Therefore, future studies should examine whether Dyrk1A also promotes tau phosphorylation with casein kinase 1.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies demonstrated that casein kinase 1␦ also phosphorylates numerous sites of tau in vitro, as GSK-3␤ does (53) and probably in vivo as well (54), suggesting that it may also play a role in tau pathology. By using double-labeled fluorescence immunohistochemistry, casein kinase 1 isoforms were found to associate differentially with neurofibrillary and granulovacuolar degeneration lesions in AD brain (55) and with tau-bearing lesions of inclusion body myositis (56). Therefore, future studies should examine whether Dyrk1A also promotes tau phosphorylation with casein kinase 1.…”
Section: Discussionmentioning
confidence: 99%
“…Several kinases known to phosphorylate-tau [89,93,94] are also accumulated within s-IBM muscle fibers, where they colocalize with p-tau-positive inclusions. These include extracellular signal-regulated kinase (ERK) [95], CDK5 [96], glycogen synthase kinase 3b (GSK-3b) [97] and casein kinase 1 [98]. Additionally, GSK-3b is hyperphosphorylated and activated in s-IBM muscle fibers [71].…”
Section: Accumulation Of Phosphorylated Taumentioning
confidence: 99%
“…Several kinases known to phosphorylate tau [69,70] are also accumulated within s-IBM muscle fibers, where they co-localize with p-tau-positive inclusions. These include extracellular signalregulated kinase (ERK), CDK5 (reviewed in [26]), glycogen synthase kinase 3β (GSK-3β), and casein kinase 1 [75]. Also, GSK-3β is hyperphosphorylated and activated in s-IBM muscle fibers [50].…”
Section: Phosphorylated Taumentioning
confidence: 99%